Factors Affecting Consumer Confidence After a Cybercrime Incident and Evaluation of Recovery Measures by Financial Institutions - Rahajeng Cahyaning Putri Cipto (Journal of Business Crime, 2025)
Objective: This study aims to explore the factors that influence consumer trust in financial institutions after a cybercrime incident and evaluate the steps taken by financial institutions to restore that trust. Research Design & Methods: This research uses a qualitative method with a literature review approach. Data was collected from various sources, including academic journals, industry reports, and news articles relating to consumer trust, cybercrime, and recovery measures taken by financial institutions. Analysis was conducted thematically to identify key factors and the effectiveness of recovery measures. Findings: The results show that consumer trust is strongly influenced by data security, the financial institution's rapid response to incidents, the institution's reputation before the incident, and the implementation of modern security technologies. Proactive communication and consumer protection programs proved effective in rebuilding trust. Implications: The findings provide insights for financial institutions on the importance of implementing strong security measures, communicating transparently with consumers, and investing in the latest technology to restore trust after a cybercrime incident. Contribution: This research contributes to the literature on consumer trust in the financial sector by identifying the key factors that influence the restoration of trust following a cybercrime incident. The findings also offer practical recommendations for financial institutions to enhance their relationships with consumers in the digital age.